Protective effects of tranilast on oxazolone-induced rat colitis through a mast cell-dependent pathway. Issue 2 (February 2016) - Chu, Hong-Qian; Li, Jun; Huang, Hong-Peng; Hao, Wei-Dong; Duan, Li-Ping; Wei, Xue-Tao
Abstract: Background: Mast cells in the gut play an important role in the innate and adaptive immune responses that are relevant to human inflammatory bowel disease. However, the contribution of mast cells to the development of inflammatory bowel disease is not well understood. This study aimed to determine the role of mast cells in oxazolone-induced colitis and to explore whether the mast cell membrane stabiliser tranilast could ameliorate colonic inflammation. Methods: Wild-type rats and mast cell-deficient rats were sensitised and challenged with oxazolone, then treated with tranilast after challenge. Controls were treated with saline. Results: Mast cell-deficient rats presented a weak response to oxazolone, while wild-type rats showed severe ulcerative colitis after stimulation with oxazolone. The mast cell-deficient rats model had a significantly lower disease activity index score than wild-type rats model (1.8 ± 1.64 vs 8.3 ± 0.58 respectively; P < 0.01). Tranilast could reduce the secretion of cytokines, immunoglobulins and myeloperoxidase activity in tranilast treatment groups compared with the model group. The number of mast cells in the wild-type model was higher than in the other groups. There was no significant change in mast cell-deficient rats. Conclusion: Mast cells play an important role in oxazolone-induced colitis. The mast cell membrane stabiliser tranilast can ameliorate oxazolone-induced colitis via a mast cell-dependent pathway.